APLIKASI KRIPTOGRAFI UNTUK MENGAMANKAN FILE AUDIO VIDEO MENGGUNAKAN VISUAL BASIC .NET - Frenky Fernando; Siswanto Siswanto; Eko Suryana (Jurnal Media Infotama, 2014)
In terms of file security is often diminished, because the file with the extension * and * .MP4 .MP3 is like the audio files that we secured was listening to the audio exams and video UAN English as exam for student/student in Ja Al-Haq is not given a security so that everyone can see the file. Application of cryptography to secure audio video files using visual basic Net made to secure the audio video files which are air-extension "* Mp3, Mp4 *" were built using the programming language Visual Basic Net. The encryption process is a process to convert the original video audio files into files that cannot be executed. Decryption process is a process to convert audio and video files into audio files randomly original video. Testing data security system is a test conducted to determine the safety data that has been integrated on a particular file, in this case the video audio file "* Mp3, * mp4".Keywords: Algorithm AES, Audio Video, Encryption, Decryption.